Four Unrecorded Species of Endophytic Diaporthe (Sordariomycetes) in Korea - Jae-Eui Cha; Ju-Kyeong Eo; Ahn-Heum Eom (Mycobiology)
Endophytic fungi associated with four plant species in Korea were isolated and characterized using morphological and molecular analyses. Phylogenetic analyses of the internal transcribed spacer (ITS) region, β-tubulin (TUB) gene, and translation elongation factor 1-α (EF1-α) gene revealed four previously unrecorded species of Diaporthe in Korea: D. caryae, D. phoenicicola, D. stewartii, and D. unshiuensis. Detailed descriptions of colony morphology and conidial characteristics are provided for each species. This study expands our knowledge of the diversity and distribution of endophytic Diaporthe in Korea and highlights the importance of these fungi in the ecosystem.